Non-invasive diagnosis of internal carotid artery dissections. Issue 2 (February 1992) - Müllges, W; Ringelstein, E B; Leibold, M
Abstract : Arteriography is thought to be mandatory for the diagnosis of internal carotid artery (ICA) dissection. With the introduction of transcranial Doppler sonography (TCD) and magnetic resonance imaging (MRI), however, this is no longer the case. In 13 consecutive patients with ICA dissections the diagnosis was made by means of non-invasive tests including extracranial and transcranial Doppler sonography, contrast enhanced computed tomography (ceCT), and, in five patients, MRI. Intra-arterial digital subtraction angiography used as the gold standard in all cases was confirmative. Extracranial and transcranial ultrasound findings indicative of the diagnosis could be identified. MRI directly demonstrated the intramural haematoma and the false lumen of the dissected artery. These non-invasive techniques also allowed for repetitive follow up examinations. They were, however, unable to demonstrate false aneurysms in the chronic state. Results show that the diagnosis of carotid dissection can be made by means of cerebrovascular ultrasound and MRI.